Independent Smallholders Farmers Group Sustain Biodiversity, Social and Economy After a Roundtable on Sustainable Palm Oil Certification: Case Study Sites in Jambi Province, Indonesia. Issue 1 (1st December 2022) - Rosyani,; Zemp, D C; Irawan, B; Ermadani,; Nizori, A
Abstract: The purpose of this research is to analyze environmental impacts by assessing the number of forest crops planted among oil palm plantations, comparing soil qualities between certified and non-certified areas, analyze economic impacts by calculating the group's income, and analyze the strategies used by strengths to be balanced biodiversity and economic development. The data collection uses observing, interviewing, and sampling the soil in the oil palm plantation and control site. The economic analysis was analyzed by using cost and benefit analysis. There has been a very significant change as the location of the river border has been planted with several types of forest plants. The chemical properties of soil in Gapoktan and non-Gapoktan farming areas were low pH or acid soil reaction. However, organic C, total N, and available P in Gapoktan soils were higher than in the non-Gapoktan soils. Smallholders' strategies can maintain the sustainable management of oil palm plantations. It can be concluded that plot scales in smallholder plantations can support the biodiversity of oil palm plantations; so that runoff water can be restrained, and the biodiversity enrichment in oil palm can generate synergies between economic, social, and ecological functions.